1978
DOI: 10.1093/jn/108.7.1071
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Urea Formation and Argininosuccinate Synthetase Activity in Rat Liver

Abstract: The circadian rhythms of the urea concentrations in urine, serum, and liver and their generation mechanism were investigated. When rats were allowed to eat freely, the urea concentration and the total urea content of the urine were higher during the night than during the day-time. Consistent with these findings, the urea concentrations in the liver and serum had circadian rhythms with the highest values at 0200 hours and the lowest values at 1400 hours. The amplitude of the rhythm increased with increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The urea concentration and the total urea content of the urine were higher during the night than during the day-time. Consistent with these findings, the urea concentrations in the liver and serum had circadian rhythms with the highest values at 02:00 h and the lowest values at 14:00 h. Argininosuccinate synthetase is considered as the rate limiting enzyme to play a critical role in regulation of urea formation, and thus it seems likely that the circadian rhythm of change in urea concentration might be caused by periodical change in the synthetase activity (Kato et al 1978).…”
Section: Biological Rhythm Research 585supporting
confidence: 60%
“…The urea concentration and the total urea content of the urine were higher during the night than during the day-time. Consistent with these findings, the urea concentrations in the liver and serum had circadian rhythms with the highest values at 02:00 h and the lowest values at 14:00 h. Argininosuccinate synthetase is considered as the rate limiting enzyme to play a critical role in regulation of urea formation, and thus it seems likely that the circadian rhythm of change in urea concentration might be caused by periodical change in the synthetase activity (Kato et al 1978).…”
Section: Biological Rhythm Research 585supporting
confidence: 60%
“…Arginine (Arg), which plays an important role in the urea cycle, also exhibits suggestive circadian rhythmicity (FDR ϭ 0.215; PT0.6) in our CE-MS data. It is also noteworthy that the final product-Urea-is reported to vary over 24 h in the blood of certain species such as rabbits (41) and rats (42). Interestingly, Reddy et al (43) showed that 3 key enzymes involved in the urea cycle, carbamoyl-phosphate synthetase 1 (CPS1), argininosuccinate synthetase 1 (ASS1), and arginase 1 (ARG1), show circadian rhythms in the liver, the center of the urea cycle and urea formation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding frequency also showed its effects on diurnal changes of some metabolite concentrations only in subjects fed twice daily compared to subjects fed by automatic distribution of concentrate (Eicher et al 1999). In rats, liver and serum urea concentrations showed circadian fluctuations that are closely related to food intake, with nocturnal acrophases (Kato et al 1978).…”
Section: Discussionmentioning
confidence: 99%